Boxing Training Robot - Ahmed Jalamneh; Ahmed Nabhan (My University, 2023)
This report presents the design and implementation of a boxing training robot with AI capabilities for punch detection and skill enhancement. The objective was to create a versatile system that provides real-time feedback and guidance to users practicing their boxing techniques. The system offers two modes: Training Mode for free practice with AI feedback on speed, accuracy, and form, and Vision Mode to simulate real-time punches when the user assumes a guard position. Software and hardware integration techniques ensure seamless communication. Experimental evaluations confirm the system's effectiveness, detecting punches in real-time and providing valuable feedback for an immersive training experience. Additionally, Vision Mode utilizes AI to detect the user's guard position, triggering the robot to simulate punches in real-time. The project demonstrates effective software and hardware integration, ensuring seamless communication among components. Experimental evaluations validate the system's punch detection accuracy and its ability to provide a valuable training experience.